2006
DOI: 10.1159/000096591
|View full text |Cite
|
Sign up to set email alerts
|

Serum Trefoil Factors in Patients with Inflammatory Bowel Disease

Abstract: Background: Trefoil factors (TFF1–3) play a critical role in mucosal protection and repair in the gastrointestinal tract. The aims of the present study were to examine associations between serum TFF1–3 and clinical and biochemical markers reflecting disease activity and to examine changes in TFF1–3 in patients with inflammatory bowel disease (IBD) before and during high-dose prednisolone treatment and tapering.Methods: Serum concentrations of TFF1–3 were quantified in 48 ulcerative colitis (UC) and 50 Crohn’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 54 publications
3
25
0
Order By: Relevance
“…Trefoil factor 1 is a secreted protein that is involved in various pathological condition including inflammatory bowel disease, 22 prostate cancer, 23 breast cancer, 24 and lung cancer. 25 Because our microarray and immunohistochemistry data indicated that TFF1 expression was specific to pancreatic cancer when compared with normal tissue and pancreatitis, we measured TFF1 in pancreatic cancer cell conditioned media.…”
Section: Discussionmentioning
confidence: 99%
“…Trefoil factor 1 is a secreted protein that is involved in various pathological condition including inflammatory bowel disease, 22 prostate cancer, 23 breast cancer, 24 and lung cancer. 25 Because our microarray and immunohistochemistry data indicated that TFF1 expression was specific to pancreatic cancer when compared with normal tissue and pancreatitis, we measured TFF1 in pancreatic cancer cell conditioned media.…”
Section: Discussionmentioning
confidence: 99%
“…The TFF3 gene, which plays a role in mucosal protection and repair in the gastrointestinal tract, is known to be induced by estrogen [42], and it is over-expressed in several types of cancer [43]. Elevated serum levels of TFF3 have been reported in inflammatory bowel disease [44] and ulceration of the upper gastrointestinal tract [45]. LGALS1 was shown to be induced by estrogen [46].…”
Section: Discussionmentioning
confidence: 99%
“…They facilitate epithelial cell migration to cover damaged areas, constrain proapoptotic signals and promote angiogenesis and leukocyte migration. TFF peptipes have been mostly studied in the gastrointestinal tract and its associated diseases of chronic inflammation such as inflammatory bowel disease, where upregulation of TFF peptides has been demonstrated [16,19]. …”
Section: Discussionmentioning
confidence: 99%
“…A non-significant trend towards increased urinary TFF2 levels in early CKD stages compared to controls was noticed and may reflect the described initial repair response and immediate clearance. In the gastrointestinal tract higher TFF peptide levels are associated with ulceration and inflammation and can be correlated with disease activity [16,19]. Similarly, TFF2 upregulation in chronic renal failure might occur to limit cell death and epithelial damage.…”
Section: Discussionmentioning
confidence: 99%